Strategi Penempatan Kapasitor Optimal Kompensasi Daya Reaktif Untuk memperoleh efisiensi Di PT. Semen Bosowa Maros - Mustafa, Syahrul; Irvawansyah, Irvawansyah; Parawangsa, Akbar Naro; Ikhsan, Muhammad (Politeknik Bosowa, 2024)
Abstract— One strategy to improve the voltage profile is by placing optimal capacitors in the right locations in the distribution system. Installation of capacitors in distribution systems is carried out for several purposes such as: improving voltage regulation, improving power factor, reactive power compensation, increasing line capacity and reducing losses. The tolerance limit for permissible stress values is 0.95 to 1.05 per unit. In this research, power quality improvements will be carried out using capacitor banks at PT Semen Bosowa Maros. The repair process is simulated using the Genetic Algorithm (GA) method. This method carries out several simulations, namely the power flow before and after installation of the capacitor bank, optimization of capacitor placement which is carried out three times with different bus candidates, to determine the location, number of capacitor capacities, and economic analysis. The selection of buses that experience voltage drops has been produced to improve the quality and voltage stability of the electrical system at PT Semen Bosowa Maros which provides a solution considering economic factors after installing the capacitor bank.